Experimental Comparison of Passivity-Based Controllers for the Level Regulation of a Conical Tank - Travieso-Torres, J (Institute of Electrical and Electronics Engineers Inc., 2016)
The techniques of adaptive passivity-based controller (APBC) and non-adaptive passivity-based controller (PBC), together with a PI controller, are applied to the level regulation of a conical tank. A comparative study considering the controller designs and experimental results is presented. A single APBC and PBC are designed for the whole operational range of the plant; whereas a PI controller with three different settings is used for level regulation at low, medium, and high operating points. The APBC design is simpler than the designs of PBC and the PI techniques, since no knowledge of the plant parameters is needed. Also, APBC is the only one showing robustness under variations of a plant parameter. © 2016 IEEE.